Tier‐1 and Tier‐2A Scenario Parameterisation and Example Calculations ‐ In Support of the Revision of the Guidance Document on Persistence in Soil under Council Directive 91/414/EEC and Parliament and Council Regulation (EC) 1107/2009 (SANCO/9188/VI/97 rev. 8, 12.07.2000) - European Food Safety Authority (EFSA Journal)
Abstract European scenarios for exposure of soil organisms to Plant Protection Products are currently not available (EFSA Panel on Plant Protection Products and their Residues (PPR), 2010). In this document, the parameterisation of realistic worst‐case scenarios for Tier‐1 and Tier‐2A simulations is described which are part of a tiered approach. The aim of this scheme is to assess such Predicted Environmental Concentrations (PEC), chosen to be the 90th spatial percentile, resulting from the use of the plant protection product. In order to account for the uncertainty in substance and soil properties, the Tier‐2A scenarios are combinations of soil and climatic properties within a zone, for which the predicted concentration is equal to the 95th percentile of all concentrations within the area of annual crops. The selected soil profiles are based on digitised information from topsoil (organic matter and texture) combined with calculated average soil profiles available in the SPADE‐1 database. The daily weather information for the scenarios is taken from the MARS database using the period 1990‐2009. In order to have a sufficient overview on the differences between simulations performed with the analytical Tier‐1 model and the numerical Tier‐2A models, PEARL and PELMO test runs are performed covering all relevant substance properties and all evaluation depths. For each of the total‐soil scenarios, both models simulate nearly the same concentration. Small differences between PEARL and PELMO can be found for the pore‐water scenarios due to differences in the calculation of soil moisture contents. The comparison with the analytical model shows that Tier‐1 concentrations are usually above the respective Tier‐2A concentrations in accordance with the philosophy of the tiered assessment scheme. However, due to the different handling of soil moisture, Tier‐1 simulations may occasionally give concentrations below those of Tier 2A, which occurrence necessitates additional calibration using special model‐adjustment factors.